Clinical case of severe ascariasis with a complicated course in pediatric practice - O. A. Gushcha; L. A. Bezrukova; L. V. Puzyreva (Детские инфекции (Москва))
Ascariasis is the most common infectious parasitic disease in childhood.  In the Omsk region, the situation on the disease of this helminthiasis can not be considered safe or even stable. Within 5 years, the rate of increase in the incidence of ascariasis in rural areas was 9.33%.The authors' team presented a clinical case of severe ascariasis, complicated by toxic-allergic dermatitis in a child aged 10 years. Allergic manifestations of helminthiasis were also nasopharyngitis, acute bronchitis, and cheilitis. The accession of a bacterial infection in the form of bilateral conjunctivitis, balanoposthitis due to a decrease in the protective factors of immunity in parasitosis was noted. Anemia 1 degree developed on the background of damage to the intestinal wall and the absorption of vitamin B 12 by ascaris.Identified defects in the management of the patient by the district service,  the timely conduct of the study of feces on helminths would lead to early diagnosis and rational treatment.